cis-4-Cyclohexene-1,2-dicarboximide: Inhibitor of phytochrome-promoted seed germination - Bewley, J. Derek (1980)
cis-4-Cyclohexene-1,2-dicarboximide (CHDC) inhibits the germination of light-requiring seeds in both light and darkness but has no effect upon the germination of non-light-requiring seeds. In lettuce seeds, CHDC inhibits the action of far-red-absorbing form of phytochrome in breaking dormancy. This inhibition can be overcome by benzyladenine and red light together, but not by a combination of red light and gibberellic acid. Gibberellic acid-induced germination of lettuce seeds in darkness is inhibited also by CHDC. Embryos isolated from dark-imbibed lettuce seeds germinate on the inhibitor. CHDC was thought to be an “analogue” of cycloheximide, but it does not inhibit protein synthesis in lettuce seeds. Our results lead us to conclude that CHDC inhibits germination of seeds that require red light to break dormancy and interferes with some aspect of metabolism that is stimulated by far-red-absorbing form of phytochrome.